Persuasive Discourse in Japanese Language Online Popeyemagazine - Rida Afifah; Yuni Masrokhah (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
In the curent 4.0 generation, language is an important aspect for everything. The variety of language use is also very diverse so it is interesting to do research. This study aims to determine the types of hyogen and types of text structures that are often used in persuasive discourse. The novelty of this research with previous research is examining hyougen which contains persuasive meanings including meirei, kinshi, irai, and kanyuu. The method used in this research is descriptive qualitative method, with data collection using the documentation method, followed by data analysis using discourse analysis techniques. The source of data from this study is hyogen in sentences contained in the online magazine popeyemagazine.jp, totaling 41 data. The result of this research is that the type of hyugen that is often used in persuasive discourse is kanyuu hyougen. While the type of text structure that is often used in persuasive discourse is the type of chuukukugata (type of middle conclusion).